1993
DOI: 10.1021/j100129a015
|View full text |Cite
|
Sign up to set email alerts
|

Laser flash photolysis studies on intramolecular hydrogen atom transfer of [(hydroxynaphthyl)propyl]benzophenone and intramolecular proton-induced electron transfer of [(methoxynaphthyl)propyl]benzophenone via triplet exciplexes

Abstract: Laser photolysis studies at 355 nm have been carried out on the intramolecular hydrogen atom transfer (intra-HT) reaction of [(hydroxynaphthyl)propyl] benzophenone, BP-(CH&-ROH, and the proton-induced intramolecular ionization (intra-pion) reaction of [ (methoxynaphth yl)propyl]benzophenone, BP-(CH2)3-ROMe, in acetonitrilewater (4:l v/v) at 295 K. After 355-nm laser pulsing to BP-(CH&-ROH and BP-(CH2)3-ROMe, the intramolecular triplet energy transfer (intra-ET) reactions from the triplet moiety (3BP*) to the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

1993
1993
1996
1996

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 12 publications
2
23
0
Order By: Relevance
“…The values of φ TET for the BP-DMNA and -DENA systems in ACN were experimentally determined to be 0.74 ((0.04) and 0.61 ((0.03), respectively, with the use of eqs 2-4. [24][25][26][27][28][29][30][31] Analogously, the triplet exciplex formation between BP and 3 DMNA* (or 3 DENA*) was expected in the present system. It is often reported that the induced quenching of 3 BP* by naphthalene derivatives competes with triplet energy transfer.…”
Section: Triplet Energy Transfer and Exciplex Formation In Acnsupporting
confidence: 77%
See 4 more Smart Citations
“…The values of φ TET for the BP-DMNA and -DENA systems in ACN were experimentally determined to be 0.74 ((0.04) and 0.61 ((0.03), respectively, with the use of eqs 2-4. [24][25][26][27][28][29][30][31] Analogously, the triplet exciplex formation between BP and 3 DMNA* (or 3 DENA*) was expected in the present system. It is often reported that the induced quenching of 3 BP* by naphthalene derivatives competes with triplet energy transfer.…”
Section: Triplet Energy Transfer and Exciplex Formation In Acnsupporting
confidence: 77%
“…[24][25][26][27][28][29][30][31]41 The rate constants for triplet energy transfer (k TET ) and induced-quenching (k IQ ) are expressed by eqs 5 and 6, respectively, since the quenching of 3 BP* consists of both triplet energy transfer and the induced-quenching processes. [24][25][26][27][28][29][30][31] Therefore, the mechanism for the triplet exciplex formation in the present system can be accounted for analogously by Scheme 1, [24][25][26][27][28][29][30][31] where k 0 and k ex are the rate constants for the decay processes of 3 DANA* and 3 (DANA‚‚‚ BP)* to the ground state (DANA abbreviated for dialkylnaphthylamine represents DMNA or DENA), respectively, k 1 and k -1 are the rate constants for the association and dissociation [ 3 BP*] max ) OD 520 / 520 The values of k TET and k IQ , which are close to the diffusion-controlled rate constant, indicate that both triplet energy transfer and the induced quenching in the present system in ACN occur in a collision process.…”
Section: Triplet Energy Transfer and Exciplex Formation In Acnmentioning
confidence: 99%
See 3 more Smart Citations